2010
DOI: 10.1002/srin.201000058
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Crystallization in Mold Slags with Varying Al2O3/SiO2 Ratio

Abstract: The present paper is an investigation into how the Al 2 O 3 /SiO 2 ratio in the compositions of mold slags influences the crystallization behavior of molten slags. The experimental work is based upon observing the crystallization events through a Confocal Scanning Laser Microscope equipped with a hot-stage. The study is motivated by the variation in crystallization that might occur in mold slags due to the pickup of alumina during continuous casting of high Al containing TRIP steels. The crystallization temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…As per the aforementioned discussions, a trend to form high melting point crystals such as Ca 2 Al 2 SiO 7 with increasing alumina content was observed. 28) This might partly explain the increase in crystallization tendency with increasing alumina content. 4) The heat flux was correspondingly decreased with increasing alumina content.…”
Section: Effect Of Alumina Content In Slag Nomentioning
confidence: 99%
“…As per the aforementioned discussions, a trend to form high melting point crystals such as Ca 2 Al 2 SiO 7 with increasing alumina content was observed. 28) This might partly explain the increase in crystallization tendency with increasing alumina content. 4) The heat flux was correspondingly decreased with increasing alumina content.…”
Section: Effect Of Alumina Content In Slag Nomentioning
confidence: 99%
“…Plant experiments on continuous casting of TRIP steels indicate that a significant change of chemical composition occurred at around 10 to 15 min after the process started and alumina pickup and silica drop seem to pass a critical point. 27) In previous studies, [28][29][30] the variations of viscosity and crystallization behaviors with increasing mAl 2 O 3 /mSiO 2 ratio have been investigated, and the experimental results indicated that these thermophysical properties changed with varying mAl 2 O 3 /mSiO 2 ratio. However, the effect of mAl 2 O 3 / mSiO 2 ratio on the slag structure has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…21) In the present work, crystallization behaviors of CaO-Al2O3-based mould fluxes with varying TiO2 content were investigated by the differential thermal analysis (DTA). Continuous cooling transformation (CCT) diagrams of mould fluxes were constructed.…”
Section: Introductionmentioning
confidence: 99%